1994
DOI: 10.1016/0735-1097(94)90498-7
|View full text |Cite
|
Sign up to set email alerts
|

IPO-V2: A prospective, multicenter, randomized, comparative clinical investigation of the effects of sulodexide in preventing cardiovascular accidents in the first year after acute myocardial infarction

Abstract: The study provides evidence that long-term therapy with sulodexide started early after an episode of acute myocardial infarction is associated with reductions in total mortality, rate of reinfarction and mural thrombus formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 26 publications
0
30
0
6
Order By: Relevance
“…Finally, heparin-like GAGs may modulate the procoagulant properties of endothelial cells through the increase of HS at the endothelial membrane level [19]. That these GAG activities may have therapeutic relevance in cardiovascular disease is supported by the reduction in total mortality, reinfarction rate and mural thrombus formation observed in patients treated with sulodexide after acute myocardial infarction [41].…”
Section: Perspectivesmentioning
confidence: 75%
“…Finally, heparin-like GAGs may modulate the procoagulant properties of endothelial cells through the increase of HS at the endothelial membrane level [19]. That these GAG activities may have therapeutic relevance in cardiovascular disease is supported by the reduction in total mortality, reinfarction rate and mural thrombus formation observed in patients treated with sulodexide after acute myocardial infarction [41].…”
Section: Perspectivesmentioning
confidence: 75%
“…Furthermore, sulodexide has other pharmacological effects potentially useful in the diabetic patients, subject to a high probability of developing acute cardiovascular diseases: anti-thrombotic activity, decrease of oxidative stress, hypolipidemic effect, prevention of glucose toxicity, suppression of cellular inflammation and anti-atheromatous effects [6]. Several clinical studies demonstrated sulodexide efficacy in patients, diabetic and not diabetic, affected by vascular diseases associated with a thrombotic risk: peripheral occlusive arterial diseases [29,30], prevention of recurrent deep venous thrombosis [31,32], diabetic retinopathy [33], diabetic foot [34,35], cerebrovascular [36,37] and cardiovascular diseases [38,39] and management of chronic venous disease, including the more severe and complicated cases such as venous ulcers [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…There has been no report of altered hemostasis concomitant with sulodexide use in these settings. [36][37][38] The chemical content of sulodexide is characteristic of heparin compounds, and the sulfate content, sulfate/carbonyl ratios, and in vitro antifactor Xa activity reported to the US Food and Drug Administration (FDA) for sulodexide are well within the required ranges. 39 However, differences between glycosaminoglycan formulations between the drug used in previous studies and that used in this study cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%